Industrial training report: Aubella (MM2H) Sdn Bhd - Mohammad Rosdi, Siti Nursyazana (Universiti Teknologi MARA, Perlis, 2024)
During my internship at Aubella (MM2H) Sdn. Bhd. from 1st March 2024 to 9th August 2024, I had the opportunity to immerse myself in the operations of a leading facilitator of the Malaysia My Second Home (MM2H) program. Established in 2006 and based in Penang, Malaysia, Aubella specializes in assisting clients with MM2H visas, accredited by the Malaysian Government, and plays a pivotal role in enhancing Malaysia's appeal as a retirement and investment destination. My internship primarily focused on the accounting department, where I aimed to apply theoretical knowledge to real-world accounting practices and contribute to enhancing the company’s internal controls. Throughout the five and a half months of internship, I manage to conducted a comprehensive SWOT analysis and financial ratio analysis for Aubella. The analysis revealed that from 2020 to 2022, Aubella had improved its liquidity but faced challenges such as a long average collection period and declining profitability due to pandemic-related revenue declines. The company also reduced debt ratios for stability but showed declining asset turnover efficiency, highlighting the company operational inefficiencies. Despite Aubella's strategic strengths in location and financial improvements, it encountered challenges such as declining profitability, operational inefficiencies, and a need for brand recognition. However, there are growth opportunities through expansion and partnerships, although the company must navigate threats posed by economic instability and regulatory fluctuations. Moreover, this internship provided numerous advantages for me including a deeper understanding of Aubella's business operations. It also underscored the importance of leveraging strengths and opportunities while addressing weaknesses and threats to maintain a competitive advantage and sustain growth. This experience has been instrumental in broadening my knowledge of financial management, internal controls, and strategic analysis within a specialized service visa industry, preparing me to apply academic knowledge to practical challenges in accounting and finance.